Brazilian Drug Information Centre: descriptive study on the quality of information 2010-2015 - Pamela Alejandra Escalante-Saavedra; Gabriela Marques-Batista; Hellen Karoline Maniero; Rachel Bedatt-Silva (Farmacia Hospitalaria)
Objective: To define the activities of the Drug Information Centre of the Federal Council of Pharmacy (Cebrim/FCP), to describe the passive information and the satisfaction of its users. Method: The centre has a computerized system for recording and storing the received questions and their answers: the Sistema de Informação Farmacoterapêutica SIFAR (Pharmacotherapeutical Information System) that generates management reports; out of these, the reports from the period 2010 to 2015 were analyzed. Results: The main activity carried out by the centre was the passive information provided to pharmacists and undergraduate Pharmacy students. The most frequent subjects were: administration and way of use of medicines and indication and drug interactions, which were answered in less than 24 hours in most cases. Approximately 80% of those users who completed the satisfaction survey rated the service provided as good and optimal. Conclusion: Cebrim/FCP provides objective, updated and timely information (passive information) on medicines for pharmacists, with administration and way of use as the most recurrent subjects, and the majority of applicants were satisfied with the service.